Forestry as a sustainable asset class for turbulent times?. (6th January 2011) - Rockemann, Christian; Schiereck, Dirk
There is good reason to anticipate increased demand for sustainable and responsible investments from both retail and large institutional investors. Increasing interest in forestry may come from both a financial and general sustainability standpoint, and from a carbon perspective, because trees are a critical part of any successful climate change strategy. We develop the true sustainable financial return (TSFR) concept for forestry investment screening which provides a good indication of long-run, sustainable return levels without leverage. Depending on investment horizon and illiquidity level, forestry investments tied to biological growth drivers seem the most attractive. Forestry then qualifies as a sustainable and responsible investment even during periods of financial crisis. In addition, we provide evidence that forestry investments can offer significant value to investors by adding a low correlation with other assets. Ultimately, the business model is proven and successful.